Effect of stavudine dosage reduction on the incidence of symptomatic hyperlactataemia/lactic acidosis in adults female HIV/AIDS infected patients treated at Dr George Mukhari Hospital - Nlooto, Manimbulu (University of Limpopo (Medunsa Campus), 2010)
With the availability of Highly Active Antiretroviral Therapy (HAART), one of the limitations of treatment safety is the occurrence of adverse events associated with antiretroviral agents. The aim of this study was to establish whether stavudine dosage reduction prevents toxicity from developing and minimizes the incidence of symptomatic hyperlactataemia/lactic acidosis (LA) in adults female HIV/AIDS infected patients. This retrospective study covered adult patients treated at the adult ARV clinic, Dr George Mukhari Hospital. The records of 88 patients aged between 27 and 59 years, initiated and treated from August 2004 to January 2006, were analyzed ( 67 females and 21 males). Twenty nine females started their treatment on a regimen containing 40 mg stavudine while 38 females were started on 30 mg stavudine. A group of male patients (n=21) were included for comparison. Seven males started on 40 mg stavudine and 14 were on 30 mg stavudine. Ten out of twenty nine females who started treatment on 40 mg stavudine developed elevated lactate levels while nineteen received 30 mg stavudine as reduced dose. Eight out of nineteen further developed elevated lactate levels when on 30 mg stavudine but eleven out of nineteen remained stable on treatment with 30 mg stavudine as reduced dose. In the group started on 30 mg stavudine, thirteen females out of thirty seven developed elevated lactate levels while twenty four were stable on their treatment. Key words: stavudine, dosage reduction, lactate levels, hyperlactataemia, lactic acidosis.
Theses (Msc.(Med.)(Pharmacy))--University of Limpopo, 2010.
Keywords: Stavudine; Dosage reduction; Lactate levels; Hyperlactataemia; Lactic acidosis